A Comparative Analysis of Mechanisms for Settlement of Election Disputes: Case Studies of Indonesia and South Africa - Sistyawan, Dwanda Julisa; Saraswati, Retno; ALW, Lita Tyesta; Sally, Novian Uticha; Jayawibawa, Marcellus (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2024)
This study provides a comparative analysis of the mechanisms for settling election disputes in Indonesia and South Africa, focusing on transparency, accountability, effectiveness, and efficiency. Despite notable democratic advancements, both nations continue to grapple with challenges that could undermine the legitimacy of electoral outcomes and democratic stability. The research investigates how transparent and inclusive these mechanisms are, the extent of public scrutiny, and the accountability measures in place for responsible parties. It also assesses the timeliness of dispute resolution, enforceability of decisions, and their overall impact on electoral integrity and legitimacy. Key findings highlight the roles of Indonesia's Bawaslu and South Africa's IEC in ensuring openness and public participation while identifying political interference, resource constraints, and procedural complexities as significant challenges. The study further explores best practices such as engaging civil society, simplifying procedures, and adopting technology to enhance dispute resolution mechanisms. Through this analysis, the research contributes to the understanding of electoral governance and offers policy recommendations to strengthen democratic institutions in Indonesia and South Africa.